KEGIATAN EKOWISATA TAMAN SARI BUWANA BANJAR BENG KAJA DESA TUNJUK KABUPATEN TABANAN SEBAGAI WUJUD PARIWISATA BERKELANJUTAN - I Putu Budiarta; I Ketut Suja (Politeknik Negeri Bali, 2014)
In accordance with future tourism, there will be a movement from mass tourism to quality tourism, as a sequence, all sectors that take part in tourism development should develop quality tourism. Ecotourism is one of the quality tourism which aims at sustainability of nature or ecology, economy and social benefit. This study aimed to know the activities of Taman Sari Buwana Ecotourism which has implemented sustainable tourism at Banjar Beng Kaja, Tunjuk Village, Tabanan Regency. Data of this study was collected by using direct observation, depth interview, and documentation. The data is obtained from informants who know the object of the study such as the Head and villagers of Tunjuk Village. After that the data was analysed descriptively. The results of the study showed that the activities of ecotourism in Banjar Beng Kaja include trekking, observing and participating way of life and traditional farming of the local people. Those activities could attract and satisfy the visitors because they could give them new experiences. In addition, they could give a positive contribution to economy, social and environment of Banjar Beng Kaja which is in accordance with the concept of sustainable tourism.